2015
DOI: 10.15439/2015f355
|View full text |Cite
|
Sign up to set email alerts
|

Control Unit for Power Subsystem of a Wireless Sensor Node

Abstract: Abstract-This paper addresses analysis of the principle of a bi-directional electric energy charge pump and describes circuit solution for control unit of a wireless sensor node power subsystem. This power and control unit, as the power subsystem of the wireless node, comprises two supercapacitors. Bi-directional energy flow between these two supercapacitors takes place in order to optimally satisfy the sensor node energy requirements. At the same time, the bi-directional energy flow enables optimal energy har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, for applications that require a long lifespan or operates in low temperatures, a combination of super-capacitors and rechargeable batteries would be optimal, as the super-capacitors have a much longer lifetime and a large range of operating temperatures (Sánchez et al 2011;Ongaro et al 2012). We note that, in recent times, energy storage in WSNs is often a combination of rechargeable batteries and super-capacitors to benefit from both the higher number of charge/discharge cycles of super-capacitors and the high energy density of rechargeable batteries (Kochlan et al 2015).…”
Section: Rechargeable Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for applications that require a long lifespan or operates in low temperatures, a combination of super-capacitors and rechargeable batteries would be optimal, as the super-capacitors have a much longer lifetime and a large range of operating temperatures (Sánchez et al 2011;Ongaro et al 2012). We note that, in recent times, energy storage in WSNs is often a combination of rechargeable batteries and super-capacitors to benefit from both the higher number of charge/discharge cycles of super-capacitors and the high energy density of rechargeable batteries (Kochlan et al 2015).…”
Section: Rechargeable Batteriesmentioning
confidence: 99%
“…Around 2010, sensor nodes with energy harvesters were introduced, which has led to the development of EH-WSNs. In these networks, the sensor node architecture is composed of one or multiple sensing units, a radio transceiver, a processing unit, an energy harvester, one or more energy storage units, a power management system, and possibly an energy predictor (Kochlan et al 2015;, as shown in Figure 2. The energy-harvesting system converts harvested energy into electrical energy for use by the sensor node, either directly (as shown in Figure 3(a)) or indirectly by first recharging the node energy storage (as shown in Figure 3(b)).…”
Section: Energy-harvesting Node Architecturementioning
confidence: 99%
“…The physical architecture of sensor node as micro-electronic device includes four basic parts; a sensing sub-system, which comes with a sensor and an ADC; a processing sub unit, that comes with a small memory area; an RF transceiver sub-system for data reception and transmission and a power unit all working as a unified system to meet the application specific intentions of the sensor network. Additionally, a sensor node may be fitted with, a location finding system such as GPS, an energy harvester to convert harvested energy into electrical energy for use by the sensor node and an actuator to facilitate node mobility [2], [3], [1]. figure 1 below depicts the components of a typical sensor node.…”
Section: Introductionmentioning
confidence: 99%